Disability and quality of life of patients with rheumatoid arthritis: assessment and perspectives - A. Stancati; F. Salaffi (PAGEPress Publications, 2011)
Functional disability and quality of life in rheumatoid arthritis (RA) are key outcomes that determine patient's demand for care, and influence their compliance and satisfaction with treatment. In the recent years the demand to collect outcome data is ever increasing as a means for the validation of quality care, and the development of effective outcome measures has become a major thrust of health research and has contributed to better understanding the relationship between outcomes and specific elements of health care. There are several disease-generic and specific instruments available that have proven valuable in outcome testing in RA. The first instruments provide a broad picture of health status across a range of conditions, whereas the latter are more sensitive to the disorder under consideration and are therefore more likely to reflect clinically important changes. When necessary, this kind of scales can be supplemented with specialised domain-specific scales (for the assessment of psychological well-being, social role functioning, or other). As in other fields, these measurement instruments mainly focus on: a) clinical signs and symptoms (physiologic and biologic); b) physical and/or cognitive functioning; c) well-being and emotional functioning; d) social functioning; e) satisfaction with care and other personal constructs (life satisfaction, spirituality, etc.); f) health-related quality of life (HRQOL). Over the past 20 years, there has been a better recognition of the patient's point of view as an important component in the assessment of health care outcomes, and an increasing interest in HRQOL as an important area of research, due to the rising burden of chronic diseases, longer expectation of life, the growing number of health intervention alternatives, and greater emphasis on humanising health care. In addition, decision-making on issues of cost-effectiveness across health inputs and resource allocation across health programs is likely to be more sound if informed by HRQOL evidence. This paper reviews the literature and discusses the major issues regarding mainly measures of physical function (e.g., mobility or daily activities) and health status, including some so called HRQOL instruments.